Clinical features and molecular genetic risk factors for the development of chronic bronchitis in adolescent smokers. - Ilchenko, S. I.; Fialkovska A. А. (Medicni Perspektivi, 2019)
Chronic bronchitis (СB) remains one of the most pressing problems of pediatric pulmonology. This is due to the high prevalence of this disease and the possible transformation into chronic obstructive pulmonary disease (COPD) in adults. Today, there is a large number of exogenous and endogenous risk factors for developing CB in children and adolescents. However, the effect of smoking on the development, clinical course of СB and the molecular genetic basis of its formation is insufficiently studied in adolescence. The purpose of the study is to investigate the clinical features of the course and genetic risk factors for the development of CB in adolescent smokers. A comprehensive survey of 107 adolescents was performed. All patients were divided into three groups. The group 1 included 40 adolescent smokers with СВ, the group 2 – 30 adolescents with СВ who never smoked, the control group included 37 conditionally healthy adolescent smokers. The study included the collection of anamnesis, an objective examination of adolescents, and a molecular genetic investigations. For statistical processing of the results obtained, the program “Statistica 6.1” was used. The results of the study showed that smoking leads to the development of СВ in adolescence and affects its course, increasing the frequency and duration of exacerbations. An association of the 2G/2G genotype of the MMP-1 (rs1799750) gene with the risk of developing СВ in adolescent smokers was detected. At the same time, it was found that the presence of the TT genotype of the CYP1A1 (T3801C) gene can be considered as a possible factor of resistance to the development of CB in adolescent smokers. The data obtained in the course of the research will help develop measures of primary prevention and individual approaches to the rehabilitation of adolescents with СВ, which will prevent the development of COPD in the future.